Association between Human Papillomavirus and Chlamydia trachomatis genital infections in male partners of infertile couples - Olivera, Carolina (2021)
The prevalence of HPV infection and its relationship with other sexually transmitted infections was analyzed in a cohort of 117 male partners of infertile couples from Cordoba, Argentina. Semen samples and urethral swabs were obtained and the infection with HPV, Chlamydia trachomatis, HSV1, HSV2, Mycoplasma hominis and Ureaplasma urealyticum was analyzed. A prevalence of HPV infection of 27.4% was found. Interestingly, infections by exclusively low risk HPV genotypes or high/intermediate risk HPV genotypes were present in 64.5% and 22.6% of cases, respectively. Low risk-HPV6 was the most frequently detected genotype. Remarkably, HPV and C. trachomatis infections were significantly associated to each other (OR: 11.55, 95% CI 1.14–117.06). No significant differences in sperm quality were found between HPV-positive and HPV-negative patients indicating that HPV male urogenital infection does not impair sperm quality. Our results show a high prevalence of HPV urogenital infection among male partners of infertile couples, and that HPV and C. trachomatis infections are reciprocal risk factors of their co-infection. Moreover, our results suggest that men constitute a reservoir for continued transmission of C. trachomatis and HPV to women highlighting the need for routine screening for these two pathogens in male partners of infertile couples.